Past, present and future of nematophagous fungi as bio agent to control plant parasitic nematodes (The Journal of Plant Protection Sciences, 2023)
Nematophagous fungi (NF) are the major antagonists of nematodes. They include nematode trapping fungi as well  as endoparasitic fungi. For more than a century scientists are studying different facets of biology of NF including  their potential as a bioagents to control nematodes. Their inconsistent success in control of nematodes in field tri als, however, is enigmatic. This paper takes a review of the researches done by various workers on the diversity,  morphology ecology, physiology of nutrition, trap formation and mechanism of nematode capture as well as prob able causes of death. The review traces the shift in the areas of research as well as ups and downs in the interest  shown by the researchers. Guide lines for organized, coordinated research to i) screen different strains of NF that  are tolerant to antagonism by other fungi, and ii) develop a bioagent based on nematophagous fungi which will  show consistent success for the controlling of phytonematodes are also suggested.
Keywords: Nematophagous fungi (NF); mechanism of trapping nematodes; antagonism; opportunistic fungi